Analisis Model Matematika PLSQ Jumlah Perokok - St. Halija; Fardinah Fardinah; Ahmad Ansar (Program Studi Matematika Universitas Sulawesi Barat, 2021)
Smoking is a habit that is favored by some people, but smoking causes health, economic, social and environmental burdens not only for smokers but also for others. This study aims to determine the mathematical model of the number of smokers, analysis of the equilibrium point of the PLSQ mathematical model of the number of smokers and a simulation of the mathematical model of the PLSQ of the number of smokers. In this study, the researcher assumed that the current smoker had a death rate caused by smoking and that the former smoker after he recovered, would not return to smoking. The results obtained are the PLSQ mathematical model of the number of smokers which produces 1 (one) smoke-free equilibrium point and 1 (one) smoker endemic point from the model. The stability analysis of the model was carried out using the Routh-Hurwitz Criteria to identify the characteristics of the eigenvalues. From the results of the stability analysis, it was found that the smoker-free equilibrium point E0 and the smokers endemic equilibrium point E1 were stable if the condition for the relationship between parameters were met. At the end of the study, a simulation model was given using the Maple application